ANALYSIS OF ABDULLAH SHER’S SONNETS (Scientific journal of the Fergana State University, 2024)
The article succinctly analyzes thenational poet of Uzbekistan, Abdulla Sher’s sonnets. Appreciation for the topic is established and a literature review is made citing scholarly works including the rootcause of sonnet structure which is in Italian poetry and its spread across world. The analysis section describes the structure and themes of several sonnets of Sher as well as their stylistic features and summarizes the main results in conclusions.